Antimicrobial Susceptibility Testing for Enterococci - Ayesha Khan; William R. Miller; Dierdre Axell-House; MUNITA SEPULVEDA, JOSE MANUEL; Cesar A. Arias (My University, 2022)
Enterococci are major, recalcitrant nosocomial pathogens with a wide repertoire of intrinsic and acquired resistance determinants and the potential of developing resistance to all clinically available antimicrobials. As such, multidrug-resistant enterococci are considered a serious public health threat.
Keywords: vancomycin-resistant enterococcus; level aminoglycoside resistance; automated microbiology system; care-associated infections; skin-structure infections; acute bacterial skin; blood culture assay; in-vitro activity; broth microdilution; penicillin-resistant; aminoglycosides; anti-bacterial agents; beta-lactams; daptomycin; enterococcus; gram-positive bacterial infections; humans; lipoglycopeptides; microbial sensitivity tests; oxazolidinones; tetracycline; vancomycin; ampicillin; antiinfective agent; beta lactam; carbapenemase; chloramphenicol; ciprofloxacin; clavulanic acid; cotrimoxazole; dalbavancin; doxycycline; erythromycin; gentamicin; imipenem; lipoglycopeptide; metronidazole; nitrofurantoin; penicillin derivative; tetracycline; tobramycin; vancomycin; aminoglycoside; antiinfective agent; daptomycin; oxazolidinone derivative; tetracycline; vancomycin; antibiotic resistance; antibiotic sensitivity; antimicrobial activity; bacterium isolate; candida albicans; clinical decision making; clinical laboratory; disk diffusion; enterococcus; enterococcus faecium; eubacterium; gene mutation; gram positive bacterium; haemophilus influenzae; innate immunity; machine learning; mic50; mic90; minimum inhibitory concentration; multilocus sequence typing; nonhuman; quality control; review; streptococcus mitis; streptococcus pneumoniae; enterococcus; gram positive infection; human; microbial sensitivity test; microbiology